Evaluation of a high‐sensitivity assay for measurement of canine and feline serum cardiac troponin I. (16th October 2013) - Langhorn, Rebecca; Willesen, Jakob Lundgren; Tarnow, Inge; Kjelgaard‐Hansen, Mads
<x xml:space="preserve">Abstract</x> Background Cardiac troponins are established as the gold standard biomarkers for acute cardiac injury. As even small elevations of cardiac troponins have prognostic relevance in people, it is important to investigate the performance of sensitive assays for use in veterinary medicine. Objectives The aim of this study was to evaluate analytical and overlap performance of a high‐sensitivity cardiac troponin I (cTnI) assay, the ADVIA Centaur CP TnI‐Ultra assay, in dogs and cats. Methods Serum samples from dogs and cats with cardiac disease or arrhythmias, along with samples of purified canine free cTnI and complexed cTnI, T, and C (cTnI‐T‐C) were used in the assay validation study. Intra‐ and inter‐assay variation, linearity under dilution, spike‐and‐recovery analysis, and detection limit were investigated to assess analytical performance. Overlap performance was evaluated based on the ability of the assay to discriminate between healthy animals and animals with cardiac disease or arrhythmias. Results Intra‐assay variation of cTnI in canine and feline serum ranged from 3.9 to 6.4% and from 4.0 to 4.8%, respectively. Inter‐assay variation ranged from 2.7 to 4.7% and from 4.0 to 7.8%, respectively. The assay demonstrated acceptable linearity under dilution within a clinically relevant range of cTnI concentrations. Spike‐and‐recovery analysis showed excessive recovery in the range 150.7%–242.0% for free cTnI and 121.1–196.3% for complexed cTnI‐T‐C, partly due to a matrix effect. Overlap performance was acceptable as animals with cardiac disease or arrhythmias (n = 45 dogs, n = 53 cats) had significantly higher cTnI concentrations than healthy controls (P < .0001). Conclusions The results confirm the ADVIA Centaur CP TnI‐Ultra assay as a valuable tool for assessing cTnI and thus myocardial injury in dogs and cats.